Smooth Muscle Tumor Originating in the Pleura: A Case Report and Updated Literature Review - Santiago Fabián Moscoso Martínez; Vadim Zarubin; Geethapriya Rajasekaran Rathnakumar; Alireza Zarineh (Case Reports in Oncological Medicine)
Smooth muscle tumors (SMTs) of the pleura are exceptionally rare. At present and to the best of these authors’ knowledge, there are only 17 cases reported in the literature. We describe a case of a 51-year-old woman who complained of left sided pleuritic chest pain. Further, computed tomography (CT) revealed a left sided localized pleural-based mass involving the 9th rib. She underwent an interventional radiology guided percutaneous core biopsy of the lesion, which disclosed a “Smooth Muscle Tumor of Undetermined Malignant Potential (SMT-UMP).” A video-assisted thoracoscopic surgery (VATS) was performed for diagnosis and treatment purposes. Resections of the pleural-based mass and 9th rib were performed. SMT-UMP was the definitive diagnosis.